Formulasi dan Uji Mutu Fisik Sediaan Pasta Gigi Ekstrak Biji Jintan Hitam (Nigella sativa): Formulation and Physical Quality Test of Toothpaste from Black Cumin Seeds (Nigella sativa) - Vika Novia Agustyani; Cikra Ikhda Nur Hamida Safitri (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Black Cumin seeds (Nigella sativa) have antibacterial activity because they contain thymoquinones, tannins, saponanins, and flavonoids. According to (Sinaga, 2018) black cumin seeds can inhibit the Streptococcous mutans bacteria that causes dental caries. The research conducted was experimental. The thick extract of black cumin seeds (Nigella sativa) is formulated into toothpaste by varying the concentration of the viscous extract of black cumin seeds (Nigella sativa). The concentration of the active substance used was 0% in the control formula, 2% in formula I, 4% in formula II, 6% in formulation III. Then performed a physical stability test of the toothpaste preparation consisting of homogeneity, pH, high foam, dispersibility, color, odor, and taste. The test was carried out for 28 days of storage. During 28 days of storage all formulations were stable, homogeneity, pH and high foam preparation were stable and met the standards. The particles are evenly distributed so that the preparation has a stable color, smell and taste. The thick extract of black cumin seeds (Nigella sativa) can be formulated into a toothpaste preparation that is stable and meets the requirements. The most stable formulation is formulation I with a concentration of 2% viscous black cumin seed (Nigella sativa) extract.